Tabersonine, a natural NLRP3 inhibitor, suppresses inflammasome activation in macrophages and attenuate NLRP3-driven diseases in mice - Xu Hao-wen; Li Wei-feng; Hong Shan-shan; Shao Jing-jing; Chen Jia-hao; Chattipakorn Nipon; Wu Di; Luo Wu; Liang Guang (Acta Pharmacologica Sinica, 2023)
Aberrant activation of NLRP3 inflammasome causes the progression of various inflammation-related diseases, but the small-molecule inhibitors of NLRP3 are not currently available for clinical use. Tabersonine (Tab) is a natural product derived from a traditional Chinese herb Catharanthus roseus that is usually used as an anti-tumor agent. In this study we investigated the anti-inflammatory effects and molecular targets of Tab. We first screened 151 in-house natural compounds for their inhibitory activity against IL-1β production in BMDMs. We found that Tab potently inhibited NLRP3-mediated IL-1β production with an IC50 value of 0.71 μM. Furthermore, we demonstrated that Tab suppressed the assembly of NLRP3 inflammasome, especially the interaction between NLRP3 and ASC. Interestingly, we found that Tab directly bound to NLRP3 NACHT domain, thereby reducing the self-oligomerization of NLRP3. In addition, we showed that administration of Tab significantly ameliorated NLRP3-driven diseases, such as peritonitis, acute lung injury, and sepsis in mouse models. The preventive effects of Tab were not observed in the models of NLRP3 knockout mouse. In conclusion, we have identified Tab as a natural NLRP3 inhibitor and a lead compound for the design and discovery of novel NLRP3 inhibitors.